„Minden szó egy világ.”: Idegen szavak a Pacsirtában - Bucsics, Katalin (Studia Litteraria, 2018)
Even though Kosztolányi was not a linguist, his concept of language – developed in several essays – has been playing a considerable role in the reception of his oeuvre even assigning him a unique mark among his contemporaries. His approach toward language as such was characteristic yet far from being static during his lifetime; the undoubted influence of historical experiences is elucidated by preceding essays (Szegedy-Maszák, M.; Bengi, L.). The recent study emphasizes one of the most characteristic and telling components of Kosztolányi’s concept, namely his ’purism’ or the rejection of using loan words in his writing. as it has been proven, his protest against loan words – declared in essays as well as the systematic avoidance of loan words in literary works – can be observed from the mid-1910s already; this tendency seems to have been restrained during the beginning of the 1920s but it thoroughly culminated by the 1930s. The study focuses on the novel Skylark (first published in 1923), an homage to the austro-Hungarian Monarchy written by an author whose grandfather took an active part in the Hungarian revolution and War of independence between 1848 and 1849. The main goal of the present study is to demonstrate that loan words frequently used in Skylark function not only as spatial but also as temporal signs; thus, instead of highlighting some foreign nature, loan words serve rather as links to a tradition that was swept away by history.